2014
DOI: 10.1111/cch.12146
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to effective early parenting interventions for attention‐deficit hyperactivity disorder (ADHD): parent and practitioner views

Abstract: BackgroundThe importance of early intervention approaches for the treatment of attention-deficit hyperactivity disorder (ADHD) has been increasingly acknowledged. Parenting programmes (PPs) are recommended for use with preschool children with ADHD. However, low ‘take-up’ and high ‘drop-out’ rates compromise the effectiveness of such programmes within the community.MethodsThis qualitative study examined the views of 25 parents and 18 practitioners regarding currently available PPs for preschool children with AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 42 publications
3
58
0
19
Order By: Relevance
“…Despite researchers recognising a qualitative approach as important for evaluating and developing health-care interventions that are perceived as appropriate by its consumers, qualitative studies used to explore parents' perspectives of psychosocial interventions are sparse. Only four qualitative studies have explored the perspectives of parents of children with ADHD (Bull & Whelan, 2006;Davis et al, 2012;Fiks, Hughes, Gafen, Guevara & Barg, 2011;Smith et al, 2015). These studies have identified aspects of intervention that may enhance parents' perceptions of appropriateness and their engagement with intervention, such as family involvement, individualised therapy, therapist support, the need to overcome logistical barriers, a positive experience of intervention and supporting parents' self-efficacy (Bull & Whelan; Davis et al; Fiks et al, Smith et al).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite researchers recognising a qualitative approach as important for evaluating and developing health-care interventions that are perceived as appropriate by its consumers, qualitative studies used to explore parents' perspectives of psychosocial interventions are sparse. Only four qualitative studies have explored the perspectives of parents of children with ADHD (Bull & Whelan, 2006;Davis et al, 2012;Fiks, Hughes, Gafen, Guevara & Barg, 2011;Smith et al, 2015). These studies have identified aspects of intervention that may enhance parents' perceptions of appropriateness and their engagement with intervention, such as family involvement, individualised therapy, therapist support, the need to overcome logistical barriers, a positive experience of intervention and supporting parents' self-efficacy (Bull & Whelan; Davis et al; Fiks et al, Smith et al).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to explore the specific needs of parents of children with ADHD (Smith et al, 2015). Broader qualitative literature has identified that parents of children with ADHD report high levels of stress, significant emotional burden, experience the negative impact of stigma and a lack of support to cope resulting in family dysfunction (Cronin, 2004;Ho, Chien & Wang, 2011;Lin et al, 2009;Mah & Johnston, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These include: High visibility and targeted ‘marketing’ through diverse and non‐traditional venues: Information about parenting programmes needs to be disseminated through non‐traditional pathways and media including the internet and radio and television advertisements. This was because parents told us in the interviews that that not all families go to local services (Smith et al., ). Flexibility of delivery and timing: Target families often had complex and sometimes chaotic lives. This can be compounded by a lack of personal organization skills and/or low mood.…”
Section: Discussionmentioning
confidence: 99%
“… Motivational interviewing and communication skills were taught to therapists to help them better engage and ‘hold’ families. Outreach to relevant professionals to encourage referrals was improved in response to parents’ responses in the interview (Smith et al., ). …”
Section: Producing a Prototype Adapted‐nfppmentioning
confidence: 99%
See 1 more Smart Citation